Effect of Anti-Emetic Combination of Sevoflurane / Propofol Anesthesia Technique in Laparoscopic Cholecystectomy - Muhammad Salman Maqbool; Muhammad Alam; Muhammad Umer Draz; Ayesha Shahid; Shumaila Ashfaq (Journal of Bahria University Medical and Dental College)
Objective: To assess symptoms of nausea and vomiting in laparoscopic cholecystectomy post-operatively, administered anesthesia by sevoflurane or propofol and to assess the effect of dexamethasone and ondansetron anti-emetic combination. Study design & Setting: It was an experimental study design conducted from 08-Oct-2017 till 11-Jul-2018 at Rawal General & Dental Hospital. Methodology: Patients were recruited in interventional groups by lottery method as n=160, with 80 cases allocated in each group. The patients with gallstones planned for laparoscopic cholecystectomy after preoperative assessment were classified to American Society of Anesthesiologist (ASA) physical status class I-II. All the patients placed in a particular ASA physical status class were (exposed to both induction methods) either anesthetic induction by propofol 1-2 mg/kg (group-A) or by employing sevoflurane 4-8% (group-B) in combination with oxygen, while maintenance was done in both study groups with 2% sevoflurane and 50% nitrous oxide in oxygen. After procedure patients stayed in post-anesthesia care unit where intra-operative monitoring was evaluated. The primary end point of the study was to note the rate of nausea and vomiting in 24 hours interval after surgery. Results: Both sevoflurane and propofol are equally effective anesthetic induction agents. The same combination of dexamethasone and ondansetron was given to both groups and so the actual effect of both anesthesia drugs in terms of side effects were nullified. Conclusion: In laparoscopic cholecystectomy, both sevoflurane and propofol are good enough when administered with dexamethasone and ondansetron anti-emetic combination, for post-operative nausea and vomiting up to 24 hours observation time in study.